Role of Socioeconomic Status in Hypertension among Chinese Middle-Aged and Elderly Individuals. (13th October 2019) - Wu, Xinyi; Wang, Zhonghua
Abstract : Hypertension is an important global health concern. The relationship between hypertension and socioeconomic status (SES) has been extensively studied. However, the role of SES in hypertension is still controversial, and this kind of study is sorely lacking among Chinese middle-aged and elderly individuals. The data of this study come from the China Health and Retirement Longitudinal Survey (CHARLS) released in May 2017. A total of 21, 126 people from all around China, with ages older than 45 years, were enrolled in the questionnaire survey. Hypertension was determined according to the entry in CHARLS ("Do you have doctor-diagnosed hypertension?"), and 17, 676 people responded to this entry. The basic demographic and SES information were collected. Multivariate logistic regression was used to evaluate the risk factors of hypertension. Concentration index was used to measure inequality of hypertension incidence. Among the investigated middle-aged and elderly individuals, 5, 177/17, 676 (29.3%) had doctor-diagnosed hypertension. Multivariate logistic regression implied that individuals older than 55 years (OR 1.436, 95% CI 1.085–1.900 for age interval of 55–64 years; OR 2.032, 95% CI 1.455–2.839 for age interval of 65–74 years; OR 1.672, 95% CI 1.031–2.714 for age interval of older than 75 years), male (OR 0.038, 95% CI 0.595–0.986), overweight (OR 2.47, 95% CI 1.462–4.183), and diabetes (OR 3.159, 95% CI 2.129–4.687) were associated with hypertension. For society support, individuals in the lowest quintile were more likely to suffer hypertension. Concentration index results suggested that different income groups did not show inequality on hypertension incidence. Elder age, male, overweight, diabetes, and poor society support were suggested to be associated with hypertension incidence among middle-aged and elderly individuals in China. Our study provides implications for controlling and managing hypertension.